Effect of red palm olein and glutinous rice flour mixture as fat replacers on the physicochemical, rheological, and microstructural properties of buffalo meat emulsion - Hasanah, Nur Nabilah (Universiti Putra Malaysia, 2024)
The present study evaluated the physicochemical, rheological, and microstructural properties of buffalo meat emulsion incorporated with red palm olein (RPO) and glutinous rice flour (GRF) as fat replacers. A total of six different samples were prepared by using combinations of RPO and GRF replacing animal fat viz., control (with animal fat), R1 (100% fat replaced by RPO), R2 (50% fat replaced by RPO), RG (50% fat replaced by 25% RPO and 25% GRF), G1 (100% fat replaced by GRF), and G2 (50% fat replaced by GRF). The samples were analysed for physicochemical parameters, gel strength, rheological and microstructural properties. G1 and G2 samples were recorded with improved emulsion stability, cooking loss, hardness, and chewiness while lowering the fat content. Micrographs of G1 and G2 samples demonstrated a spongy/honeycomb-like structure with roughly spherical crystalline granules. The rheological properties of G1 indicated a more stable emulsion with a higher storage modulus (G’). Using RPO as a fat replacer seemed to produce a lower-quality emulsion. Therefore, replacing the fat with GRF, especially at 100%, is proposed for buffalo meat emulsion.